Career opportunities [videorecording (DVD)] - Whaley, Frank, 1963-; Connelly, Jennifer; Mulroney, Dermot; Mulroney, Kieran (MCA/Universal Home Video, 1998)
A smooth-talking small town guy with a knack for putting up a front, finds himself locked inside the local department store with the daughter of the town's wealthiest family.